2013
DOI: 10.1097/mpg.0b013e31829fad06
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Circulating Carnitine Status of Preterm Infants Fed Fortified Human Milk or Preterm Infant Formula

Abstract: Objective: The aim of the study was to compare plasma carnitine profiles in fortified human milk (HM)-fed preterm infants or formula-fed preterm infants. Methods: Plasma acylcarnitine concentrations were determined in 20 formula-fed and 18 HM-fed preterm infants (birth weights between 1000 and 2200 g) by isotope dilution ESI MS/MS technique on study days 0, 14, and 28.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Furthermore, the higher contents of acyl-carnitine C8.1, C12.0 and 14.0 in infants receiving the IF might be related to its higher content of medium-chain fatty acids. Similar observations were reported in the study by Bene et al, in which plasma concentrations of medium-chain acyl-carnitines were related to the formula content of medium-chain triglycerides [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the higher contents of acyl-carnitine C8.1, C12.0 and 14.0 in infants receiving the IF might be related to its higher content of medium-chain fatty acids. Similar observations were reported in the study by Bene et al, in which plasma concentrations of medium-chain acyl-carnitines were related to the formula content of medium-chain triglycerides [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Issues in establishing life-stage DRIs for bioactives vary greatly from one substance to another. For example, in infants, intakes from human milk bioactive substances such as nucleotides [25], carnitine [2], lutein [3], and glycoconjugate sugars [19, 26] have been used to derive safe levels of addition of such compounds to infant formulas. Evidence of the biological benefit of addition of these substances to the health of formula-fed infants is inconsistent, but no adverse effects have been identified.…”
Section: What Are the Challenges To Establishing Such A System And Homentioning
confidence: 99%
“…However, phenylalanine, tyrosine and tryptophan proportions were unchanged. However, Bene J et al 24 didn't find any difference in plasma carnitine profiles in pre-term infants fed with fortified human milk.…”
Section: Discussionmentioning
confidence: 92%
“…However, threonine was significantly higher in bovine group and proline and ornithine was significantly higher in ultra-filtrated human milk protein group Similar results were reported by other researchers. [20][21][22][23][24] Gathwala G et al 19 in his study also used blood urea nitrogen as biochemical markers for assessment of efficacy of fortification and found that blood urea nitrogen was significantly high in fortified group (22.80 ± 2.65 mg/dL) as compared to non-fortified/control group (21.12 ± 2.77 mg/dL) after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%